Penggunaan Teknologi Blockchain dalam Jaringan Kom-puter untuk Meningkatkan Keamanan Data - Fauzan Prasetyo Eka Putra; Tryamina Salsabila; Syahdayana Arifin; Seindi Pujiastutik D. (Pusat Riset dan Inovasi Nasional, 2025)
The rapid development of information technology requires computer network systems to have a high level of data security. One of the technologies that is developing and has great potential in terms of data security is blockchain. Blockchain technology offers a decentralized and transparent system that can minimize the risk of data manipulation and leakage. This study aims to analyze the implementation of blockchain technology in computer networks and its impact on improving data security. The methods used in this study are literature studies and simulations of blockchain-based network implementations. The results of the study show that the integration of blockchain into computer networks can improve data integrity, authentication, and availability through cryptographic hash mechanisms, smart contracts, and consensus systems. However, challenges such as transaction speed and power consumption are still obstacles to widespread implementation. Thus, blockchain technology has significant potential in strengthening computer network data security, but requires further development to optimize its perfor-mance